NEW RECORDS FOR THE FAUNA AND ZOOGEOGRAPHY OF CUCKOO WASPS (HYMENOPTERA: CHRYSIDIDAE) IN THE LOWER VOLGA REGION (Acta Entomologica Serbica, 2022)
The fauna and zoogeography of chrysidids in the steppe and forest biocenoses of the Lower Volga region in the Saratov region were studied, which include 92 species and 2 subspecies from 17 genera: Cleptes – 2 species; Colpopyga – 1; Elampus – 8; Haba – 1; Hedychridium – 6; Hedychrum – 5; Holopyga – 11; Omalus – 2; Philoctetes – 3; Pseudomalus – 5; Chrysidea – 1; Chrysis – 41; Chrysura – 3; Spinolia – 1; Stilbum – 2; Trichrysis – 1 and Parnopes – 1, among which 69 species are presented for the Saratov region for the first time. Two species, Chrysis corusca Valkeila, 1971 and Chrysis vanlithi Linsenmaier, 1959, and one subspecies Chrysis frivaldszkyi sparsepunctata du Buysson, 1895, are new records for the Russian fauna. The obtained data broaden the understanding of the fauna and diversity of Chrysididae in the Saratov region and the Lower Volga region and supplement the fauna list of the Chrysididae of Russian fauna.